Effect of Shallot Extract on the Growth of Cocoa Cuttings from Sulawesi 01 Clone Orthotropic Shoots - Ahmad Naufal Zayin Amrullah; Nisa Budi Arifiana; Rahmawati (Politeknik Pertanian Negeri Samarinda, 2025)
Cocoa (Theobroma cacao L.) is a key plantation commodity, with Indonesia being one of the world's largest producers. This study aimed to evaluate the effect of shallot (Allium ascalonicum L.) extract concentrations as a natural plant growth regulator on the vegetative growth of cocoa cuttings derived from Orthotropic Shoot Cocoa (OSC) of Sulawesi Clone 01. The research was conducted from August 2024 to January 2025 at the Seed Technology Laboratory Nursery, Jember State Polytechnic. A non-factorial Randomized Complete Block Design (RCBD) was used, consisting of five treatments: 0% (control), 25%, 50%, 75%, and 100% shallot extract concentrations, each with five replications. Observed parameters included survival percentage, shoot height, and dry biomass weight. The results showed that shallot extract had no significant effect on the survival percentage of cuttings. However, it had a significant to highly significant effect on shoot height at 60, 90, 120, and 150 days after planting (DAP), and on dry biomass weight. The best vegetative growth was observed at 100% concentration (BM4), followed by 75% (BM3). This suggests that the auxin and nutrient content in shallot extract can enhance cell metabolism and growth, thereby supporting better shoot development and biomass accumulation. In conclusion, shallot extract has potential as an organic plant growth regulator to improve cocoa cutting performance, particularly at concentrations between 75% and 100%